2019
DOI: 10.1108/ijefm-02-2018-0013
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between runner environmental paradigm and their motives to participate in an urban or rural marathon

Abstract: 2017-006 Room: Oxford

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…Consistency -accounts for 10% of the variances. The analysis of the factors focused around this variance leads us to a conclusion that these motifs of the runners' behaviours can be described by the well-known in psychology rule of commitment and consistency (Cialdini, 2016). In this case, the runners' commitment and their participation in the virtual run resulted from the fact that they had already decided to take part in this event, by signing up for the traditional run.…”
Section: The Determinants Of the Engagement Of Runners In The Co-crea...mentioning
confidence: 88%
“…Consistency -accounts for 10% of the variances. The analysis of the factors focused around this variance leads us to a conclusion that these motifs of the runners' behaviours can be described by the well-known in psychology rule of commitment and consistency (Cialdini, 2016). In this case, the runners' commitment and their participation in the virtual run resulted from the fact that they had already decided to take part in this event, by signing up for the traditional run.…”
Section: The Determinants Of the Engagement Of Runners In The Co-crea...mentioning
confidence: 88%
“…In turn, Davies et al (2019) and Song et al (2012) highlight the importance of attendees' environmental awareness in their decision to participate in sustainable events. Following previous findings that a direct relationship exists between more developed world areas and greater sustainability awareness (Park et al , 2012), the current research model anticipated that attendees living in more developed world areas would tend to adopt more positive attitudes towards event sustainability.…”
Section: Discussionmentioning
confidence: 99%
“…The scale consists of 37 items grouped under nine factors, including "self-enrichment", "travel exploration", "skill mastery", "social needs", "destination attributes", "stress relief", "aggression", "competition", "physical fitness". Davies et al (2019) showed how environmental consciousness motives impact individuals' intention to participate in a rural or urban marathon using STMS. Their study confirmed that social needs, self-enrichment, and aggression are all associated with participation intentions.…”
Section: Literature Review and Hypotheses Formulation 21 Travel Motives Of Active Sports Touristsmentioning
confidence: 99%